Pemikiran Politik Islam Muhammad Asad dalam Konteks Zaman Modern - Kustiawan Kustiawan; Nanda Cahya P.; Natasya Ingga Johna; Desty Yulanda Jonnata; Laura Laura (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study analyzes Muhammad Asad's Islamic political thought, which seeks to unite Islamic spiritual values with modern political thought. Asad rejects the limited view that considers Islam merely a ritualistic religion, and asserts that Islam is a value system that governs various aspects of life, including politics and government. Using a qualitative approach and library research methods, this study explores Asad's ideas on the Islamic state, democracy and shura, social justice, and the interaction between religion and the state. The findings of this study show that Asad views the Islamic state as an ethical entity that upholds justice, the rule of law, and moral responsibility. The concept of shura is understood as a type of moral democracy based on the values of justice and public participation. Asad also emphasizes that social justice is an important aspect of Islamic government that supports the welfare of society. Asad's thinking rejects both extreme secularism and absolute theocracy, and offers a model of Islamic politics that is rational, participatory, and based on morality. The relevance of this thinking lies in its ability to provide solutions to the crisis of ethics and justice in modern politics through a combination of spirituality and rationality in government.